Lived Experience Participation in Suicide Prevention Activities in Australia, a Scoping Review - Hayley Purdon; Tania Pearce; Bess Jackson; Sarah Wayland; Myfanwy Maple (Health Expectations)
ABSTRACT Introduction Lived experience inclusion is considered best practice in suicide prevention activities. Despite this, research remains limited exploring how individuals with lived experience actively engage in suicide research and prevention activities. The current scoping review aimed to map and summarise the existing literature describing the ‘how’ of lived experience participation in Australia. Methods A scoping review according to the methodology of Arksey and O'Malley (2005) was undertaken with descriptive (e.g., study aims and methodology) and descriptive analytic data (such as key definitions and participation descriptors) being extracted from included studies. Results A total of 42 studies met the inclusion criteria and were published between 2016 and 2023. There were many gaps in the data extracted, with participation descriptors and definitions often not reported in the literature. The included studies lacked clear and consistent definitions and practices when involving people with lived experience. Conclusion Current processes for reporting experiences of lived experience participation in suicide prevention lack standardisation within peer‐reviewed publications. This review notes that there are gaps in the literature; however, the evidence base is growing for research that reports on suicide prevention research and activities that involve people with lived experience. Patient or Public Contribution This study was created and undertaken by a PhD candidate with lived experience of thoughts of suicide, suicide attempt and caring for a loved one through suicide. A further team member has lived experience of being a suicide attempt survivor, continued thoughts of suicide and carer of family with suicidal thoughts. The study was informed by a Community Advisory Committee, of which four members have lived experience of suicide, with the remaining two having lived experience in areas where inclusion is paramount such as disability and suicide research. Ethics approval was not required for the participation of the Community Advisory Committee as they were providing advice only on the research conduct.